2020
DOI: 10.3390/v12070752
|View full text |Cite
|
Sign up to set email alerts
|

Serosurveillance and Molecular Investigation of Wild Deer in Australia Reveals Seroprevalence of Pestivirus Infection

Abstract: Since deer were introduced into Australia in the mid-1800s, their wild populations have increased in size and distribution, posing a potential risk to the livestock industry, through their role in pathogen transmission cycles. In comparison to livestock, there are limited data on viral infections in all wildlife, including deer. The aim of this study was to assess blood samples from wild Australian deer for serological evidence of exposure to relevant viral livestock diseases. Blood samples collected across ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 53 publications
(78 reference statements)
1
26
0
Order By: Relevance
“…A thorough understanding of the diversity of viruses, their transmission routes, and their tropism in wild deer provides epidemiologic baseline information about potential pathogenic threats for humans, domestic animals, and other wildlife species. The present study complements our initial work about the viral investigation in wild deer across multiple geographic locations in Australia [ 29 ]. Picobirnaviruses were detected via deep sequencing analysis of a small group of deer serum and plasma samples, with subsequent molecular screening being performed in a range of specimens collected from wild deer in southeastern Australia, as well as in faecal samples from cattle.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…A thorough understanding of the diversity of viruses, their transmission routes, and their tropism in wild deer provides epidemiologic baseline information about potential pathogenic threats for humans, domestic animals, and other wildlife species. The present study complements our initial work about the viral investigation in wild deer across multiple geographic locations in Australia [ 29 ]. Picobirnaviruses were detected via deep sequencing analysis of a small group of deer serum and plasma samples, with subsequent molecular screening being performed in a range of specimens collected from wild deer in southeastern Australia, as well as in faecal samples from cattle.…”
Section: Discussionmentioning
confidence: 58%
“…This study used samples collected as part of a disease investigation in Australian wild deer [ 29 ]. Briefly, blood samples were collected during culling of fallow deer ( Dama dama ) in the Liverpool Plains and rusa deer ( Rusa timorensis ) at Wollongong, New South Wales ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…BEFV is considered endemic and known to cause an epizootic disease in many regions, such as East Asia [45], Japan [19,24], China [16,27], the Philippines [28], Thailand [6], Taiwan [21,31,44], Australia [15,17], India [38], Israel [11,47], Jordan [20], Iran [3,5], Kingdom of Saudi Arabia [50], South Africa [37], and Turkey [9,36]. For example, previous studies performed in Australian deer reported serological evidence for BEFV in red deer [12] and another study conducted in Australia demonstrated that all samples screened in wild deer were PCR-negative for BEFV, although BEFV is endemic in Australia [22]. Serological evidence of BEFV has also been reported in a variety of species, including cattle [1,13,30,48,49], water buffalo, gazelle, Persian fallow deer [4], and yak [34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that multiple deer species (red deer, white-tailed etc., both wild and farmed) are susceptible to BVDV infections with many prevalence studies identifying animals positive for BVDV antibodies. While the numbers sampled have generally been small, seroprevalence studies have detected antibodies to BVDV in the range of 3% of deer from the eastern seaboard of Australia [ 94 ] to 63.5% in Mexican white tailed deer [ 95 ]. In addition, deer identified as positive for antibodies to BVDV have been detected in countries including Austria [ 96 ], New Zealand [ 97 ], Denmark [ 98 ], Spain [ 99 ], Germany [ 100 ], the UK [ 101 ] and the US [ 102 , 103 , 104 , 105 ].…”
Section: Bovine Viral Diarrhoea Virus In Non-bovine Speciesmentioning
confidence: 99%